Enby Experiences of Weight and Weight Sitgma: The Shape of Gender Beyond the Binary - Rinaldi, Jen; Friedman, May (Canadian Woman Studies/les cahiers de la femme, 2023)
This photo essay presents results from a digital storytelling project about trans experiences of weight stigma. We present summaries, excerpts, and still-images from three digital stories that explore the relationship between non-binary gender identity and body weight/shape/size.